Solution‐NMR Characterization of Outer‐Membrane Protein A from E. coli in Lipid Bilayer Nanodiscs and Detergent Micelles. Issue 7 (1st April 2014) - Sušac, Lukas; Horst, Reto; Wüthrich, Kurt
Abstract X‐ray crystallography and solution NMR of detergent‐reconstituted OmpA (outer membrane protein A from E. coli) had shown that this protein forms an eight‐stranded transmembrane β‐barrel, but only limited information was obtained for the extracellular loops. In NMR studies of OmpA in two different detergent micelles, "NMR‐invisible" amino acid residues in‐between the extracellular loops and the β‐barrel prevented complete structural characterization. Here, we show that this NMR‐invisible ring around the β‐barrel of OmpA is also present in lipid bilayer nanodiscs and in mixed micelles with a third detergent, thus suggesting that the implicated rate processes have a functional role rather than representing an artifact of the protein reconstitution. In addition to sequence‐specific NMR assignments for OmpA in the nanodiscs, the present results are based on a protocol of micro‐coil TROSY‐ and CRINEPT‐type NMR diffusion measurements for studying the hydrodynamic properties and the foldedness of [2H, 15N]‐labeled membrane proteins in nanodiscs. This protocol can be applied under conditions closely similar to those used for NMR structure determinations or crystallization trials.